Contribuição ao estudo dos constituintes químicos da própolis de Eucalyptus urophilla da região do Triângulo Mineiro - Bezzan, Lélia Cordeiro Freire (2000)
Propolis is a resinous mixture consisting of products collected by bees. It’s known that bees collect resin from several plant species. Brazilian propolis have good prices in International commerce by its higher medicinal value, especially those produced near a eucalyptus forest. This work studies a sample of propolis and a sample of exudate collected in a forest of Eucalyptus urophilla. There were no other species near the place from where the samples were collected, at least at 300 m. Water, methanol and chloroform were used as solvents to prepare the resin and propolis extracts. The methanolic extracts were employed to determinate total phenolics compounds and total flavonoids. A silica-gel chromatographic column (CC) was prepared with ciclohexane and 0,5 g of methanol propolis extractives were added in the column. This column was eluted with chloroform, acetone and methanol. Volatile compounds were investigated in the aqueous extract using Clevenger apparatus. The chloroform extract was used in wax quantification and in GC/MS investigation. The propolis wax was analyzed by FTIR. The methanolic extract was washed with ethyl acetate and soluble portions were separated by CC. A final insoluble residue was obtained. This residue was analysed by GPC, FTIR, solid State 13C NMR spectroscopy and CHN. Ash determination was quantified on the residue. CG/MS was the most useful tool applied in this work. All samples were prepared with derivatization methods like methylation and silylation. One compound was isolated in this work. Behenic acid was obtained in the silica gel column eluted with ciclohexane. This compound was identified by melting point tests and IR spectra. Fifty- ii five compounds were identified in propolis and twelve in the Eucalyptus exudate. The propolis and exudate extracts analysed did not present the same compounds as assumed. Further analysis of the aqueous extracts from both samples is being carried out in order to comprove that. Solid-state 13C NMR spectroscopy shows no signals of phenolic carbon in the residue resulting after the solvent extraction. The ashes quantity, volatile-free dry residue, volatile and wax compounds are in good agreement with other samples from Brazilian propolis. However, lower quantities of total phenols and flavonoids were found in the propolis studied when compared with another sample extracted in the surroundings of a Eucalyptus citriodora forest in São Paulo State.